Neutrophil Extracellular Traps Promote the Development of Intracranial Aneurysm Rupture. Issue 6 (5th April 2021) - Korai, Masaaki; Purcell, James; Kamio, Yoshinobu; Mitsui, Kazuha; Furukawa, Hajime; Yokosuka, Kimihiko; Miyamoto, Takeshi; Sato, Hitomi; Sato, Hiroki; Eguchi, Satoru; Ai, Jinglu; Lawton, Michael T.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Potential roles for neutrophils in the pathophysiology of intracranial aneurysm have long been suggested by clinical observations. The presence of neutrophil enzymes in the aneurysm wall has been associated with significant increases in rupture risk. However, the mechanisms by which neutrophils may promote aneurysm rupture are not well understood. Neutrophil extracellular traps (NETs) were implicated in many diseases that involve inflammation and tissue remodeling, including atherosclerosis, vasculitis, and abdominal aortic aneurysm. Therefore, we hypothesized that NETs may promote the rupture of intracranial aneurysm, and that removal of NETs can reduce the rate of rupture. We employed both pharmacological and genetic approaches for the disruption of NETs and used a mouse model of intracranial aneurysm to investigate the roles of NETs in the development of intracranial aneurysm rupture. Here, we showed that NETs are detected in human intracranial aneurysms. Both global and granulocyte-specific knockout of peptidyl arginine deiminase 4 (an enzyme essential for NET formation) reduced the rate of aneurysm rupture. Pharmacological blockade of the NET formation by Cl-amidine also reduced the rate of aneurysm rupture. In addition, the resolution of already formed NETs by deoxyribonuclease was effective against aneurysm rupture. Inhibition of NETs formation with Cl-amidine decreased mRNA expression of proinflammatory cytokines (intercellular adhesion molecule 1 [ICAM-1], interleukin 1 beta [IL-1β], monocyte chemoattractant protein-1 [MCP-1], and tumor necrosis factor alpha [TNF-α]) in cerebral arteries. These data suggest that NETs promote the rupture of intracranial aneurysm. Pharmacological removal of NETs, by inhibition of peptidyl arginine deiminase 4 or resolution of already-formed NETs, may represent a potential therapeutic strategy for preventing aneurysmal rupture.